2015
DOI: 10.1021/nn505214f
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Critical Growth of High Quality Nitrogen Doped Graphene on Dielectrics by Plasma-Enhanced Chemical Vapor Deposition

Abstract: Nitrogen doping is one of the most promising routes to modulate the electronic characteristic of graphene. Plasma-enhanced chemical vapor deposition (PECVD) enables low-temperature graphene growth. However, PECVD growth of nitrogen doped graphene (NG) usually requires metal-catalysts, and to the best of our knowledge, only amorphous carbon-nitrogen films have been produced on dielectric surfaces by metal-free PECVD. Here, a critical factor for metal-free PECVD growth of NG is reported, which allows high qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
128
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 50 publications
4
128
0
1
Order By: Relevance
“…PECVD can achieve the controllable synthesis of the large‐area graphene on dielectric substrate. Recently, graphene has been grown on various substrates containing metals SiO 2 /Si sapp, hire, mica, h‐BN for applications in FETs 34, 39, 50, 52, 64, 125. PECVD grown graphene films on transition metals have similar growth process (dissolution precipitation and surface catalyzed dissociation) with thermal CVD grown graphene films, thus have comparable field effect motilities.…”
Section: Applications Of Graphene Grown By Pecvdmentioning
confidence: 99%
See 2 more Smart Citations
“…PECVD can achieve the controllable synthesis of the large‐area graphene on dielectric substrate. Recently, graphene has been grown on various substrates containing metals SiO 2 /Si sapp, hire, mica, h‐BN for applications in FETs 34, 39, 50, 52, 64, 125. PECVD grown graphene films on transition metals have similar growth process (dissolution precipitation and surface catalyzed dissociation) with thermal CVD grown graphene films, thus have comparable field effect motilities.…”
Section: Applications Of Graphene Grown By Pecvdmentioning
confidence: 99%
“…However, the amorphous nitrogen doped carbon film normally suffers from poor electrical transport and gate modulation due to its disordered structure. Recently, the crystal growth of nitrogen‐doped graphene (NG) has been achieved in NH 3 /CH 4 plasma 125. The FETs of NG are fabricated using the growth substrate as the dielectric and gate electrode.…”
Section: Applications Of Graphene Grown By Pecvdmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Several PECVD studies have been reported on SiO 2 , 27-38 quartz, 27,31,38 glass, 34,39 and Al 2 O 3 28,38 to explore the synthesis of graphene without metal catalysts at low temperature. Successful enlargement of isolated grain sizes has been realized using twostep growth in PECVD process.…”
Section: -24mentioning
confidence: 99%
“…[28][29][30] Other groups tried to grow continuous graphene using PECVD. However, these lms suffered from common problems such as many defects, less surface uniformity, [31][32][33][34][35][36][37][38][39] and three-dimensional (3D) nanowall growth.…”
Section: -24mentioning
confidence: 99%